1998 Kansas Worker Protection Standard Pesticide List - Cress, Donald C. (My University, 1998)
This publication lists the pesticides, herbicides, fungicides, insecticides, etc. that are registered with the Kansas Department of Agriculture for uses and it includes ones that have triggered requirements to have the Worker Protection Standards on their label.
MF2121_1998_05
Keywords: MF2121; Health and Safety; Crops; Equipment and structures.; MF